Biostratigraphic and palaeoenvironmental significance of a rich tetrapod fossil accumulation in the Lower to Middle Burgersdorp Formation of the Karoo Basin. (February 2023) - Wolvaardt, Frederik P.; Hancox, P. John; Browning, Claire; Strong, Michael
Abstract: Almost forty years of field investigations on the farm Lemoenfontein, near Aliwal North in the southern Free State Province of South Africa, have recovered a diverse amniote fauna from rocks of the Burgersdorp Formation that are assigned to the lower Middle Triassic Trirachodon-Kannemeyeria Subzone of the Cynognathus Assemblage Zone (AZ). In total, 140 skulls and articulated skeletons of seven tetrapod taxa have been collected, along with more recently collected details about their depositional environmental setting. Trace fossils including three different burrow casts, each with distinctive geometries, were also collected and documented. The amniote specimens include both juveniles and adults of the procolophonids Teratophon spinigenis and Thelephon contritus; the rhynchosaur Eohyosaurus wolvaardti; bauriid therocephalian Microgomphodon oligocynus ; and the cynodonts Cricodon kannemeyeri and Trirachodon berryi. The diverse fauna is dominated by largely herbivorous tetrapods, mainly procolophonids, all with dentitions adapted to browse fibrous plant material. The only carnivore present is a small unidentified basal cynodont. Several of these tetrapods have previously been proposed as burrowers. The diversity and abundance of well-preserved fossils provide new insight into how palaeoenvironmental and behavioural factors contributed to the hyper-accumulation of tetrapod fossils at this site. Whilst the herbivorous dicynodont Kannemeyeria simocephalus and carnivorous erythrosuchid archosaur Erythrosuchus africanus are common components of the middle Cynognathus AZ Trirachodon-Kannemeyeria Subzone elsewhere in the basin, they are absent from the lower exposures at Lemoenfontein, which suggests that the fossil assemblage represents a transitional fauna from the Langbergia-Garjainia and Trirachodon-Kannemeyeria Subzones. Another interesting aspect of the site is that all the tetrapod remains are of individuals of small body size. This apparent Lilliput effect supports the view that the faunal recovery after the Permian-Triassic mass extinction in the Karoo Basin was only fully developed by Middle Triassic times. Highlights: A lower-Middle Triassic Karoo Basin field site hosts a hyperaccumulation of fossils. This fossil assemblage yields biostratigraphic and palaeoenvironmental insights. It consists of procolophonids, rhynchosaurs, therocephalians and cynodonts. These tetrapod taxa show small body size and herbivorous dentition. This Lilliput fauna was transitional after the end-Permian mass extinction event.